Prediction of subway shield construction parameters based on multi-layer perceptron - LI Wenqian; WU Yunhuan; WU Jingye; CHEN Zhihuai; XIE Senlin; HU Anfeng (Shenzhen Daxue xuebao. Ligong ban)
Shield construction technology has been widely used in subway construction, and reasonable prediction of shield tunneling parameters is of great practical significance for improving construction safety and reducing operational difficulties.Taking a section of the Hangzhou Airport Express Underpass Tunnel as the engineering background, this study uses the friction angle, cohesion force, compression modulus and heaviness of the soil layer within the diameter of the tunnel as well as the burial depth of the tunnel cover, the preset blade speed and propulsion speed of the shield machine as inputs, and the slurry volume, slurry pressure, soil discharge volume, total thrust force and blade torque during the shield construction as outputs, and establishes a prediction model of shield tunneling parameters based on a multi-layer perceptron.By comparing the predictive performance of the model under different combinations of hyper-parameters on the dataset, a suitable shield construction parameter prediction model is selected for the project.The model predictive effect is verified using the measured data, and the predicted values are consistent with the overall variation pattern of the measured data, with an average error within 20%.The established multi-layer perceptron model provides reasonable predictions with good accuracy and can be applied to predict shield tunneling parameters under the conditions of composite strata.